Unilateral congenital dysplasia of lung associated with vascular anomalies. Issue 4 (July 1973) - Hislop, Alison; Sanderson, M.; Reid, Lynne
Abstract : Hislop, A., Sanderson, M., and Reid, L. (1973). Thorax, 28, 435-441. Unilateral congenital dysplasia of lung associated with vascular anomalies. In three cases of unilateral lung dysplasia the structural changes have been analysed quantitatively to throw light on the nature of the anomaly and stage of its appearance. In one case the pulmonary artery was hypoplastic and the systemic supply normal but increased, suggesting onset in late intrauterine life or early childhood: in the other two cases the blood supply was only systemic, from both normal and abnormal arteries, suggesting onset in the early weeks of intrauterine development. Airway development was consistent with this interpretation. All cases had additional signs of maldevelopment of mesodermal tissue. The origin of the various types of systemic artery is discussed.